MINIMUM WAGE AND PAY SYSTEM FOR PUBLIC SECTOR ORGANISATIONS (The Role of Exact Sciences in the Era of Modern Development, 2023)
In this article, accounting and reporting in budgetary organisations cannot be imagined without an automated accounting programme. The reason is that the amount of information that needs to be processed daily in budget organizations is increasing, and scientific recommendations for their use in UzASBO program and the introduction of payroll accounts have been developed.